Determinan Audit Delay Berdasarkan Kondisi Internal Perusahaan Manufaktur di Indonesia - Nurfitriani Nurfitriani; Yayu Putri Senjani (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
This study aims to analyze the effect of profitability, solvency, firm size, internal audit and audit committee on audit delay in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The samples in this study are manufacturing companies that meet certain criteria that have been determined using purposive sampling method with a total sample of 285 observational data. The data analysis technique used is panel data regression analysis which is processed using Eviews v.10. Based on the data analysis, it shows that profitability, company size and internal audit have a negative effect on audit delay, while solvency and audit committee have no effect on audit delay.